Characterization and pre-treatment of Jatropha curcas seed cake for co-firing with coal - Madanayake, Buddhike Neminda (2017)
In the light of growing concern over greenhouse gas emissions and limited fossil fuels, the use of renewable energy sources such as biomass is becoming more vital. Jatropha curcas seed cake, which is a waste product of biodiesel production, has been identified as a potential candidate to be co-fired with coal in existing boilers. There is a dearth of information on the effective utilisation of Jatropha curcas seed cake in this manner, and this research work contributes to bridging this knowledge gap. The seed cake received was divided into two distinct classes based on appearance and texture, identified as type A (harder and lower oil content) and type B (the more abundant class). As an initial step, the fundamental fuel properties of the seed cake were determined; these include the proximate and ultimate analyses, higher heating value (HHV) and inorganic content. The HHV of type A and type B was 20.76 MJ/kg and 24.06 MJ/kg, respectively; their dry ash content was 5.9% and 4.4%, respectively. K was the most abundant inorganic element present.